Round and flat zygomatic implants: effectiveness after a 1-year follow-up non-interventional study - Carlos Aparicio; Waldemar D. Polido; James Chow; Rubén Davó; Bilal Al-Nawas (SpringerOpen, 2022)
Abstract Introduction There are few zygomatic implants (ZI) designs available. The objective of this non-interventional study was to report the effectiveness of two new site-specific ZI, selected and placed following the zygoma anatomy-guided approach (ZAGA). Materials and methods Consecutive patients presenting indications for rehabilitation using ZI were treated according to ZAGA Concept recommendations. Implants were immediately loaded following the manufacturer's instructions. Success criteria regarding prosthetic offset, rhino-sinus status, soft tissue condition, and implant stability were additionally used as outcome parameters. Results Twenty patients were followed for a period of 12 to 28 months (average 18.8 months). Ten received 2 ZI plus regular anterior implants; One received 3 ZI plus regular implants and nine received 4 ZI. In total, 59 ZI were placed, 34 (58%) Straumann ZAGA-Flat design, and 25 (42%) ZAGA-Round. Forty-nine percent of the sites were classified as ZAGA-4 type and 27% as ZAGA-2. Four patients (20%) presented discontinuities of the sinus-nose floor before surgery and 15 patients (75%) presented previous sinus opacities. All implants bar one reached more than 45 N.cm of insertion torque. No surgical complications were observed. After 1 year, the modified Lund-Mackay score was negative in 17 patients. Seventeen sites in 11 patients exhibited decreased opacity when pre-surgical imaging was compared to 1-year post-surgical CBCT. All implants and prostheses remained stable and in function. Conclusions The study concluded 100% implant/prosthesis survival rates and low complication levels. Within the limitations of the sample and observation period, results suggest that even in cases of extremely resorbed maxillae (as per cases in this study), ZAGA-Flat and ZAGA-Round ZI are viable treatment options when restoring atrophic maxillae following the ZAGA protocol.